X-shaped radio galaxies: probing jet evolution, ambient medium dynamics, and their intricate interconnection - Giri, Gourab; Fendt, Christian; Thorat, Kshitij; Bodo, Gianluigi; Rossi, Paola (Frontiers in Astronomy and Space Sciences, 2024)
This review explores the field of X-shaped radio galaxies (XRGs), a distinctive subset of winged radio sources that are identified by two pairs of jetted lobes which aligned by a significant angle, resulting in an inversion-symmetric structure. These lobes, encompassing active (primary) and passive (secondary) phases, exhibit a diverse range of properties across the multiple frequency bands, posing challenges in discerning their formation mechanism. The proposed mechanisms can broadly be categorized into those related either to a triaxial ambient medium, into which the jet propagates, or to a complex, central AGN mechanism, where the jet is generated. The observed characteristics of XRGs as discovered in the most substantial sample to date, challenge the idea that there is universal process at work that produces the individual sources of XRGs.Instead, the observational and numerical results rather imply the absence of an universal model and infer that distinct mechanisms may be at play for the specific sources. By scrutinizing salient and confounding properties, this review intends to propose the potential direction for future research to constrain and constrict individual models applicable to XRGs.